The left hand side and its role in hammer throw technique (Coaching Track & Field Athletics)
Hammer throwers and coaches alike often look at the right hand side of the body as the principle driving force of hammer throw technique, and with good reason. The right hand side through the double support phase drives the acceleration of the implement.